Giving Positive Reinforcement to Reduce Aggressiveness in Children with ADD - Muhamad Fadlullohil Hakim Nurdiyanto (International Consortium of Education and Culture Research Studies, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) is a medical condition, which is characterized by hyperactivity, inability to focus attention and impulsivity, which is persistent. The location of this research is located at SDN Jimbaran Wetan. The child is male and he is currently seven years old. ADHD children now sit in the first grade of Jimbaran Wetan Elementary School. The purpose of this study was to determine the effect of giving positive reinforcement to the decrease in aggressiveness in ADHD children. The variables of this study are positive reinforcement as an independent variable (X) and aggressiveness as a dependent variable (Y). The Positive Reinforcement Method is a method in which the child with ADHD is given a task to control himself and if the task can be done then the child gets a reword that has been agreed upon in advance, such as if the child shows a good attitude on that day then the child gets a toy gift. This study uses a qualitative experimental approach with within-subject research, namely the type of experimental research that examines an individual's behavior, makes observations, and set a baseline, then intervenes. After the intervention, the researcher made another observation to determine the effect of the intervention. Observations were made just before the intervention, during the intervention and after the intervention using the aggressiveness check list. In filling out the check list, researchers involve class teachers to help control and supervise children with ADHD. Class teachers are also involved to fill the aggressiveness check list so they can find out about changes in the daily behavior of ADHD children in the intervention process. From the results of data analysis it was found that there was a decrease in aggressiveness in children with ADHD. This is indicated from the aggressiveness check list which illustrates that the aggressiveness behavior is increasingly decreasing.